Assessing MBG Economic Spillovers Through Parents, Canteens, and MSMEs - Putri, Rahma Sarlita Ramadhani; Kurnia, Yola; Monika, Citra; Aliyah, Zahrah; Antolin, Ferdino Franklyn; Hamid, Muhammad Farhan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the economic impact of President Prabowo’s Free Nutritious Meal (MBG) Program on local communities, particularly focusing on shifts in economic activity within schools and surrounding areas. The purpose of this research is to identify how the MBG program influences school canteen operators, nearby MSMEs, and parents or guardians who indirectly benefit from the policy. A mixed-method design was employed, combining semi-structured interviews with three respondent groups and quantitative data analysis to strengthen field findings. The results reveal that the MBG program creates economic opportunities for MSMEs involved in the food supply chain but also poses challenges for school canteens and businesses that are not partnered with the program due to declining student purchases and intensified competition. Moreover, increased demand from MBG vendors has raised raw material prices, affecting small-scale businesses. Meanwhile, parents report reduced daily food expenses and improved nutritional intake for students. The study implies that the MBG program has the potential to strengthen local economies if its implementation ensures equitable access, fair distribution of opportunities, and sustainable partnerships between schools and community-based enterprises.